Comparative study on the heat transfer characteristics of spray cooling in confined spray chambers. (5th January 2020) - Xie, J.L.; Ranjith, K.; Wong, T.N.; Lee, H.M.
Highlights: Effects of spray environment on spray cooling in confined spaces were investigated. Maximum heat flux enhancement of 62.3% was achieved by enlarging the spray volume. Negligible effect of spray volume on the maximum steady-state heat flux was found. Abstract: Spray environment can exert significant influences on the heat transfer of spray cooling, particularly in extremely confined spaces. In this paper, the heat transfer performance of two confined spray chambers was explored in a refrigerant cycle with R134a as the coolant. The benchmark chamber had an utmost confined spray volume of 1.76 mL which was anticipated to encounter flooding situations at the flow rates ranging from 6.12 to 6.56 mL/s. Hence, a new spray chamber modified from the benchmark chamber to include an additional liquid storage reservoir and improved discharging outflow was proposed to eliminate the flooding effects. Experimental results showed that the new spray chamber with the larger internal volume and better flow management significantly enhanced the phase change heat transfer. In comparison to the benchmark chamber, the maximum heat flux enhancements achieved by the new spray chamber were 43.7% and 62.3% respectively at the compressor frequency of 30 Hz and 40 Hz, and the corresponding enhancements of evaporation fraction were 24.1% and 46.6%, respectively. However, it was found that the last operational steady-state heat fluxes before the incidence of critical heat flux (CHF) were comparable between these two spray chambers possibly due to their unique internal flow characteristics.